Analysis of Small-Scale Tofu Industry Wastewater Characteristics for Optimal Wastewater Treatment: Analisis Karakteristik Limbah Cair Pada Industri Tahu Skala Rumahan untuk Pengolahan Limbah Cair yang Optimal - Sethiavi Rizki; Wilma Nurrul Adzillah; Zulfa Amala (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Small-scale tofu industries have the potential to pollute the environment with the liquid waste generated during the tofu-making process. Liquid waste from the tofu industry has COD and BOD concentrations of up to 9,308 mg/L and 3,191 mg/L, respectively, which exceed the quality standards set forth in Ministry of Environment Regulation No. 5 of 2014. This study aims to identify and analyze the characteristics of liquid waste in the tofu industry to determine the appropriate treatment method based on the BOD/COD ratio. The research was conducted by collecting samples using the grab sampling method, followed by an analysis of the results of the waste characteristic tests. Based on the research results, it was found that one of the liquid wastes from the tofu industry in Karawang Regency had COD and BOD values of 6,062.5 mg/L and 570.5 mg/L, respectively, with a BOD/COD ratio of 0.09. These conditions prevent the direct application of biological treatment and necessitate pre-treatment in the form of physical or chemical treatment combined with biological treatment, such as wastewater treatment using filtration and constructed wetlands.